Immunoexpression of cytokeratin 19 in oral cavity mucous smear of filter cigarette smokers - Meira, Isra; Widyaputra, Sunardhi; Dardjan, Murnisari (Padjadjaran Journal of Dentistry, 2008)
Smoking has become general habits in social life. One popular kind is filtered cigarette. As the base component is tobacco without clove and separated by the filter on it. Long irritation from heat and a toxic component of cigarette changed in oral mucosa epithelial. This condition can stimulate the increase of progenitor cells, which is marked by immunohistochemistry staining method of cytokeratin 19. This descriptive study is to find the expression of cytokeratin 19 in oral mucosa cytoplasm epithelial of filter cigarette smokers. There were 30 smokers which were selected with certain criteria. Samples were taken from a cytological smear of mucosa epithelial then stained with immunohistochemistry method. Analysis has taken by calculating the number of cells in the cytological smear. Then the immunoexpression of cytokeratin 19 was known from the percentage of cytoplasm cells which have brown colour compared with a total number of cells. In conclusion, the smoking filter cigarette would increase the number of progenitor cells from chronic inflammation, which is marked by cytokeratin 19 expression in oral mucosa cytoplasm epithelial of smokers.